2014
DOI: 10.1016/j.febslet.2014.03.014
|View full text |Cite
|
Sign up to set email alerts
|

StRemorin1.3 hampers Potato virus X TGBp1 ability to increase plasmodesmata permeability, but does not interfere with its silencing suppressor activity

Abstract: Edited by Tamas DalmayKeywords: Remorin Plant membrane rafts Triple Gene Block protein 1 Potato virus X Potato virus Y Tobacco mosaic virus Plasmodesmata Viral suppressor of RNA gene silencing a b s t r a c tThe Triple Gene Block 1 (TGBp1) protein encoded by the Potato virus X is a multifunctional protein that acts as a suppressor of RNA silencing or facilitates the passage of virus from cell to cell by promoting the plasmodesmata opening. We previously showed that the membrane raft protein StRemorin1.3 is abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 37 publications
(60 reference statements)
8
61
0
1
Order By: Relevance
“…REMs form a large plant-specific protein family with characteristic PM nanodomain localisation patterns (Jarsch et al, 2014). Moreover, different members of this family have previously been associated with plant-microbe interactions (Raffaele et al, 2009; Lefebvre et al, 2010; Tóth et al, 2012; Perraki et al, 2012, 2014; Bozkurt et al, 2014) and with SERK-dependent processes (Gui et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…REMs form a large plant-specific protein family with characteristic PM nanodomain localisation patterns (Jarsch et al, 2014). Moreover, different members of this family have previously been associated with plant-microbe interactions (Raffaele et al, 2009; Lefebvre et al, 2010; Tóth et al, 2012; Perraki et al, 2012, 2014; Bozkurt et al, 2014) and with SERK-dependent processes (Gui et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…The mislocalization of these two GPI-anchored PD proteins results in an excessive amount of PDC deposition. Additionally, disruption in lipid rafts can affect the targeting of other lipid raft–enriched proteins such as Grain setting defect1 (GSD1), Remorins (REMs) and StRemorin1.3 which modulates PDC levels [82,83,84]. It was shown that GSD1 regulates PD conductance by interacting with ACTIN in association with the PDCB [84].…”
Section: Discussionmentioning
confidence: 99%
“…The atsrp1_1 (SALK_148081) and atsrp1_2 (GK-309G05) T-DNA mutants were obtained from the ABRC seed stock center, and homozygous lines were selected by PCR genotyping (primer sequences are provided in Table S1). For transient transformation, Nicotiana benthamiana leaves or 4-day-old A. thaliana seedlings were infiltrated with Agrobacterium tumefaciens cell cultures as described in Perraki et al (2014) or Marais et al (2015) respectively.…”
Section: Methodsmentioning
confidence: 99%